Modal Sosial Keagamaan dan Partisipasi Perempuan Muslim Indonesia dalam Perburuhan - Nida, Rahma; Yunisvita, Yunisvita; Gustriani, Gustriani (UI Scholars Hub, 2024)
In recent years, the muslim majority countries’ focus on women’s labor force participation has grown, particularly Indonesia which stands out with its high female labor force participation rate. We aim to shed light on the relationship between religion and work decisions in Indonesia, employing data from the World Value Survey and utilizing logistic regression analysis. Our findings reveal that active participation in religious activities positively affects muslim women’s likelihood of working part-time and in the agricultural sector. Through the results, policymakers and relevant stakeholders can consider leveraging religious organizations as potential channels for promoting women’s labor force participation.